ANALISIS DESAIN KEMASAN LOLOH CEMCEM DALAM PENINGKATAN NILAI PRODUK MELALUI PENDEKATAN ESTETIKA KOMUNIKASI VISUAL - I Komang Angga Maha Putra; Made Arini Hanindharputri (Jurnal Nawala Visual, 2020)
Loloh cemcem is a typical herbal drink from the tourist village of Penglipuran, Bangli Regency, Bali which has good health properties for the body, such as preventing heartburn and providing freshness. This drink is widely traded, but its packaging only uses bottles that resemble mineral water bottles, so that many tourists view this cemcem loloh drink as unhygienic, less aesthetic, and different from similar drinks. Penglipuran Village is a tourist village that is always visited by hundreds of tourists per day, should be able to create an increase in sales from loloh cemcem. When viewed from the character of consumers who are currently the millennial generation, visual appearance is certainly one of the attractions in choosing a product. Therefore, it is necessary to analyze the packaging design of loloh cemcem to increase the value of the product using a visual communication aesthetic approach. The trial was conducted on consumers and prospective consumers of the loloh cemcem drink to get feedback using existing packaging designs with new packaging design innovations, as data analysis taking into account the visual communication aesthetics of each loloh cemcem packaging design. This research is expected to provide additional benefits to the knowledge of visual communication design, in this case, packaging design, so that it can be used as a reference for further research. The research method used in determining the research topic, determining the problem based on internal and external factors, data collection, data analysis, and conducting trials to obtain the expected research reports and outputs. The results of the research are in the form of Loloh cemcem packaging prototypes, and how the packaging can increase the value of Loloh cemcem products.